Rapid identification of Listeria monocytogenes by cell surface protein based indirect ELISA - BHILEGAONKAR, K N; BACHHIL, V N; KUMAR, ASHOK; AGARWAL, R K (The Indian Journal of Animal Sciences, 2014)
An indirect plate ELISA was developed using polyclonal antibodies directed against crude cell surFace protein (CSP) extract,,68 kDa esp, 64 kDa CSP, 43 kDa CS,P and whole formalin killed cells (WFC) of Listeria monocytogenes 4b (MTCC 1143), Minimum detection levels of heat killed L. monocytogenes cells by the standardized test were 105; 106,. 107, 106 and 108 cells/ml for anti-crude esp, anti 68, anti 64, anti 43 and anti WFC sera, respectively, The cross reactivity of these sera was assessed with 39 cultures comprising L. monocytogenes-ll, other Listeria spp.-9 and other Gram positive and negative organisms-19. The results revealed that antibodies directed against 64 kDa CSP were more specific for L, monocylogenes than the other sera, These antibodies identified all L. monocytogenes isolates and did not cross react with any other bacteria except one positive and a weak positive reaction with L. seeligeri and L. innocua. respectively. Anti 43 kDa. anti crude CSP and anti WFC sera showed cross- reactions with many bacteria in Cluding other,Listeria spp. Antibndies against 68 kDa CSP crossreacted only. with L. ivanovii, L. innoclia and L. welshimeri. The rndirect plate ELISA using antibodies directed against 64' kDa CSP in conjunction with PI-PLC assay can be used for rapid identitication of L. monocylogenes.